Forensic age estimation using conventional radiography of the medial clavicular epiphysis: A systematic review. (April 2021) - Shedge, Rutwik; Kanchan, Tanuj; Warrier, Varsha; Dixit, Shilpi Gupta; Krishan, Kewal
Of the many roles that forensic anthropologists and medico-legal professionals need to perform, forensic age estimation is one of the most frequent and important. Scoring medial clavicular epiphyseal (MCE) fusion is a method used to estimate age in young adults. The aim of this systematic review is to assess the reliability and reproducibility of MCE fusion visualised by conventional radiography and scored by Schmeling's grading system to determine whether an individual has attained the age of 18 years. Four articles were acquired after screening 4589 articles across four databases, and these were subjected to qualitative and quantitative synthesis. The risk of bias was calculated in the qualitative synthesis using the QUADAS-2 tool. Horizontal box plots were constructed to see whether MCE fusion as visualised by conventional radiography can be used to ascertain whether an individual has attained the age of maturity (18 years). It was observed that stages 4 and 5 of the Schmeling's method of age estimation from MCE fusion are observed only in individuals aged ≥18 years. This indicates that MCE fusion, when visualised using x-rays, which are associated with less ionisation radiation compared to computed tomography, can be used to verify the attainment of the age majority in individuals.